Effect of plant growth promoters and micronutrients on growth and productivity of wheat (Triticum aestivum) varieties - PRAJAPATI, SUNIL KUMAR; VERMA, V K; SINGH, SHIVENDRA; SINGH, GURWAAN; SIDDIQUI, M Z; KHAN, NAUSHAD; SAIKIA, NILUTPAL (The Indian Journal of Agricultural Sciences, 2025)
The experiment was conducted to evaluate the influence of plant growth promoters and micronutrient on growth and yield parameters of wheat varieties. It can be concluded from the study that, DBW-187 and K-1006 demonstrated significantly higher growth and yields, with increasing grain yields by 9.87% and 2.41%, respectively, compared to K-607. The application of micro-nutrient mixture (Zn, Fe, B and Cu) resulted in the most favourable outcomes specifically, productive tillers (+11.90) and grain yield (+13.84). In general the application of various PGPs, including micronutrients, GA, seaweed extract, and nitrobenzene, led to significant increase in productivity of wheat varieties.